INFLUENCE OF THE CALL FORWARDING BUSY SERVICE ON THE TRAFFIC DISTRIBUTION IN THE GROUP OF TELEPHONE CHANNELS - MITIĆ, Dragan; LEBL, Aleksandar; TRENKIĆ, Branimir; MARKOV, Žarko (Yugoslav Journal of Operations Research; Vol 27 No 1 (2017), 2016)
In this paper we consider the influence of a call forwarding service on the traffic process in modern telecommunication networks. We analyse in detail only the case when the called user is busy. It is proved that call forwarding not only increases utilization of servers and the percent of successful calls but it also increases the call loss. On the simple example, we showed that this call loss increase is greater in the case of local (internal) and incoming calls, but smaller in the case of outgoing calls. The reason for such behaviour is in the role of call forwarding function in the case of internal and incoming traffic. In that situation call forwarding function decreases the effect of limited number of users on the decrease of offered traffic, comparing to the case of internal and incoming traffic without call forwarding (Engset traffic model). This statement is illustrated by comparative graphics of traffic loss without call forwarding function, and with this function when considering, separately, internal, incoming, and outgoing traffic.